The Effect of Project-Based Learning (PjBL) Models on Improving Students' Understanding of Concepts, Retention, and Social Attitudes - Martha Berhitu; Johanis F Rehena; Hasan Tuaputty (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2020)
The Project-Based Learning (PjBL) model is oriented to problem identification, project implementation, and product presentation. This study aims to determine the effect of PjBL learning models and conventional learning on the understanding of student concepts, retention and social attitudes of students of SMA 1 Ambon. The sample in this study were students of class XI IPA-1, totaling 39 students and class XI IPA-3, totaling 39 students in the 2017/2018 Academic Year. The research design used was a nonequivalent pretest-posttest control group design. Data analysis uses inferential statistics, namely the One Way ANOVA test. One Way ANOVA test results showed that the significant value of understanding concepts, retention, and social attitudes was 0,000<0.05. Based on the results of the study, it was concluded that there was an influence of the learning model on the understanding of concepts, retention, and social attitudes of Grade XI students of SMA 1 Ambon in studying the concept of the excretion system.